(untitled) (Philological Studies, 2019)
The planet Solaris, through its Ocean has the capacity to draw the strongest records of the brains of the crew, and these records are mostly connected with emotions of sadness, pain, pleasure. From them, it creates their partner/opponent that reflects not only theirs, but also own limits. As a method for extracting records, the Ocean, uses the dream, one of the human activities that are always correlated with the mystical, supernatural, alchemical. In psychology, the dream is a language of the unconscious and from there Ocean pulls information. It pulls without censorship in human terms of speaking